Language Technologies Handbook - Hugh, Robert Ed. (USA: States Academic Press, 2021)
Language Technology is the study of the manner in which electronic devices or computer programs can analyze, create, alter or react to human speech and text. It is an interdisciplinary field that encompasses various sub disciplines of linguistics and computer science.
Includes Bibliographical references and index.
Keywords: Language and Languages-Study and Teaching--Technological Innovations--Educational Technology--Educational Innovations